2023
DOI: 10.4081/hls.2023.11817
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between mental workload and nurse stress levels in hospitals

Zahid Fikri,
Adelia Bellarifanda,
Sunardi Sunardi
et al.

Abstract: High mental workload implies significant mental resources and can lead to increased cognitive stress and fatigue. Nurses have the responsibility of managing a wide range of nursing care tasks, which frequently involve addressing anxiety, handling patient complaints, and managing patient defense mechanisms, all of which can lead to increased stress levels. This study aimed to identify the relationship between mental workload and the stress level of nurses in the Hospital Malang City. The research utilized a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Enhancing employees' stress management skills is logical to address stress limits. A study on mental workloads and stress levels by Fikri et al (2023) found that such skills can lessen the impact of high mental workload. Optimizing worker efficiency involves factors like personal commitment and creative self-efficacy, as shown in a study by Sarwat & Abbas (2020).…”
Section: Workload Improvement Perspectivesmentioning
confidence: 99%
“…Enhancing employees' stress management skills is logical to address stress limits. A study on mental workloads and stress levels by Fikri et al (2023) found that such skills can lessen the impact of high mental workload. Optimizing worker efficiency involves factors like personal commitment and creative self-efficacy, as shown in a study by Sarwat & Abbas (2020).…”
Section: Workload Improvement Perspectivesmentioning
confidence: 99%